Minced Nerve Tissue in Vein Grafts Used as Conduits in Rat Tibial Nerves - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Introduction: Peripheral nerve injuries are encountered frequently in clinical practice. In nerve repair, an end-to-end suture is the preferable choice of treatment. However, where primary closure is not possible, the defect is to be repaired with a nerve graft. Methods: A total of 21 female Wistar rats weighing 230 to 290 g were used in the study. They were classified into the following 3 groups: (I) nerve graft, (II) vein graft, and (III) minced nerve graft. In group I, after exposure of the tibial nerve, a 1-cm-long nerve gap was created on the tibial nerve, and the defect was repaired epineurally by using the autogenous nerve. In group II, the 1-cm tibial nerve defect was repaired by using an autogenous vein graft. In group III, a 1-cm nerve graft was divided to 3 equal parts, with one of the nerve parts being minced with microscissors and placed in the vein graft lumen. Thereafter, a 1-cm tibial nerve defect was repaired by the vein graft filled with minced nerve tissue. The tibial function indices (TFIs) were calculated for functional assessment using the Bain-Mackinnon-Hunter formula. Light and electron microscopic evaluations were performed for morphometric assessment. In addition, the myelinated fibers were counted in all groups. Results: The TFIs of group II were found to be the lowest among all the groups after the sixth week, whereas the TFI of group I was found to be better than the other groups after the sixth week. There was no difference in TFIs between group I and group III. On the basis of the number of myelinated fibers, there was no statistically significant difference between group I and group III, whereas the difference was significant (P < 0.05) between groups I/III and group II. Presence of peripheral nerves in light microscopic evaluation revealed normal characteristics of myelinated fibers in all groups. The myelinated axon profile was near normal in the nerve graft group in electron microscopic evaluation. However, there were more degenerated axons with disturbed contours and vacuolizations in the vein graft group compared to the minced nerve graft group. Conclusions: We can conclude that using minced nerve tissue in vein grafts as a conduit increases the regeneration of nerves (almost like the nerve graft group) and it may not be caused by donor-site morbidity. It can be used in the repair of nerve defects instead of autogenous nerve grafts after further experimental evidence and clinical trials.
Keywords: nerve regeneration; nerve repair; nerve graft; minced nerve; vein graft; conduit; SCHWANN-CELLS; REGENERATION; REPAIR; MOTOR; GAP; RECONSTRUCTION; ENHANCEMENT; PHYSIOLOGY; PATHWAY